A calcined shell powder used for minimizing aluminum concentration in the soil of tea plantations. Issue 1 (31st December 2022) - Liu, Jianhua; Li, Weihang; Walayat, Noman; Liu, Shulai; Ding, Yuting; Song, Shuang
ABSTRACT: In this study, the effect of shell powder on the adsorption and desorption behavior of aluminum in soil of tea plantations was explored. With increasing amounts of shell powder, the adsorption of the aluminum by the soil gradually increased. As the initial pH value of aluminum solution increased, the amount of soil aluminum adsorption gradually increased. The Elovich equation was the best fitting curve for the two soil adsorption kinetics, while the best fitting curve for the desorption kinetics of the original soil (OS) was a double constant equation. The best fitting curve for OS and shell powder (SS) was the Freundlich equation and Langmuir equation, respectively. The theoretical maximum adsorption capacity of OS and SS on aluminum was 975.0 and 4191 mg/kg, respectively. In conclusion, the addition of shell powder can improve the aluminum adsorption capacity of the soil and reduce the activity of aluminum in the soil.